Limestone reaction in sandy soil: Rate effects, limestone type, moisture regime, and time - Flávia Cristina dos Santos; Álvaro Vilela de Resende; Johnny Rodrigues Soares; João Hebert Moreira Viana; Monna Lysa Teixeira Santana; Silvino Guimarães Moreira; Manoel Ricardo de Albuquerque Filho (Agrosystems, Geosciences & Environment)
Abstract An experiment was conducted in the greenhouse facilities of Embrapa Maize and Sorghum to evaluate the limestone reaction in sandy soil based on rates, limestone type, effective calcium carbonate equivalent (ECCE), and moisture regime over time. A factorial design of 4 × 2 + 3 was adopted, consisting of four limestone rates with 76% ECCE (0, 1, 2, and 4 Mg ha−1), two irrigation types (daily and monthly, simulating constant and intermittent moisture regime), and three additional treatments (three rates of “filler” limestone—99% ECCE—under monthly irrigation). Soil chemical characteristics were analyzed at 1, 2, 3, 6, and 12 months after treatment application. Soil fertility improved at the first month after treatment application, with emphasis on higher limestone rates, monthly moisture regime, and filler lime stone. The highest limestone rate did not increase the pH above 7.0. The recommended limestone rate was insufficient to elevate Ca + Mg levels to the adequate level for current production genotypes and systems, which demand higher standards. These outcomes reinforce the need for carrying out further studies and potential revision in liming recommendations for sandy soils.